Deregulation of the Transcriptional Repressor E2F6 in Myocardium Leads to Gene Activation and Dilated Cardiomyopathy - Rueger, Jennifer (Université d'Ottawa / University of Ottawa, 2011)
The E2F family of transcription factors regulate cellular growth, death and differentiation, but their role in cardiac biology remains to be fully explored. We hypothesized that the balance of the E2F pathway would determine cardiac development and function. We provide evidence for this via modulation of the E2F6 repressor, in a transgenic (Tg) mouse model. Targeted expression of E2F6 in the heart led to dilated cardiomyopathy (DCM) and death. Microarray analysis revealed that E2F responsive pathways were activated in Tg mice. Furthermore, we found that E2F6 and YY1 (E2F-co-factor) were translocated to the nucleus in Tg mice, providing a potential mechanism for the observed transcriptional activation. We also observed a marked decrease of Connexin43 protein in the myocardium, and reduced atrial conductivity in Tg mice which may lead to reduced cardiac function. The data demonstrates a novel role for E2F pathway outside of cell cycle control in the heart.
Keywords: E2F6; gene expression; dilated cardiomyopathy; microRNA